KREATIVITAS BARISTA DALAM PERACIKAN KOPI DI RR CAFE PEKANBARU - Siltri Wawenti; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
RR Cafe Pekanbaru is one of the cafes with fairly busy guest visits, this is because the coffee menu served is a variety of which is prepared by a trained barista from the cafe. The importance of a barista's creativity in creating a cup of espresso and a beautiful painting of art on the coffee foam greatly affects the quality of the coffee. The research was conducted to see the creativity of a barista in preparing a cup of coffee. This study uses qualitative methods, while the data analysis techniques in this study use observation, in-depth interviews and documentation. The key information in this study were 3 baristas. The purpose of this research is to analyze deeply the creativity of RR Café baristas who have succeeded in creating delicious coffee tastes so that the RRcafe is crowded with guests from any circle. Keywords: Creativity, Barista, Coffee and Cafe.